2020
DOI: 10.3390/educsci10090220
|View full text |Cite
|
Sign up to set email alerts
|

Behind an Accelerated Scientific Research Career: Dynamic Interplay of Endogenous and Exogenous Forces in Talent Development

Abstract: This study looks at the educational experiences, from the preschool years to advanced professional training in STEM fields, of a targeted sample of 10 (7 male, 3 female) early college entrants in China who later became professors at prestigious USA research universities. The purpose of the study was to find out (1) what some identifiable endogenous factors were about these individuals that facilitated the success of their accelerated learning and development; (2) what kinds of exogenous factors (e.g., environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…These results generally agree with several studies such as those of Dai and Li (2020) and Gierczyk and Pfeiffer (2021) on the role of teachers and the educational environment as effective exogenous factors of talent development in different fields.…”
Section: Findings and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results generally agree with several studies such as those of Dai and Li (2020) and Gierczyk and Pfeiffer (2021) on the role of teachers and the educational environment as effective exogenous factors of talent development in different fields.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…Focusing on the talent development paradigm and the contributions of its theories, this development process is based on the dynamic interaction between many endogenous and exogenous factors. Internal factors are associated with individuals, including their different abilities such as leadership abilities, whereas the latter is associated with the environment; the most important of which is the educational environment, including teachers and educators as its most important components (Dai & Li, 2020;Gagne, 2021a, b;Gierczyk & Pfeiffer, 2021;Paik et al, 2018;Swanson et al, 2020). Recent studies are shifting towards talent development and exploring the aspects related to it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bamberger (1986) studied the crisis of those musically talented teenagers whose intuitive approach to music (i.e., CA) has to be replaced by a more analytical mode of processing. In my current study of early college entrants who later became distinguished science, technology, engineering, and mathematics (STEM) researchers (Dai & Li, 2020), their college experiences are marked by a distinct, sometimes difficult, transition from being a good student (i.e., CA) to being an aspiring research scientist (i.e., MA). In her treatise on “beyond modularity,” Karmiloff-Smith (1992) argued that mental representation of experience and knowledge ultimately has to go beyond an implicit process to reach a consciously and technically controlled level of mastery.…”
Section: The Role Of Adaptive Effort In Developing Human Potentialmentioning
confidence: 99%
“…This early college entrance program admits a highly selective group of academically talented students with an average age of 15 years. The first study (Dai et al, 2015) focused on a cohort of students who entered and graduated from the program in the first decade of this century, and the second study (Dai & Li, 2020) obtained a targeted sample of early college entrants from different cohorts of the program who later became professors at first-tier research universities in the United States. We found that, across cohorts of the program, these early college entrants unanimously reported that they were cognitively challenged despite the fact they were top students in secondary school.…”
Section: The Role Of Adaptive Effort In Developing Human Potentialmentioning
confidence: 99%